2017
DOI: 10.1073/pnas.1607215114
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic Fc receptor TRIM21 inhibits seeded tau aggregation

Abstract: Alzheimer's disease (AD) and other neurodegenerative disorders are associated with the cytoplasmic aggregation of microtubuleassociated protein tau. Recent evidence supports transcellular transfer of tau misfolding (seeding) as the mechanism of spread within an affected brain, a process reminiscent of viral infection. However, whereas microbial pathogens can be recognized as nonself by immune receptors, misfolded protein assemblies evade detection, as they are host-derived. Here, we show that when misfolded ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
167
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 160 publications
(177 citation statements)
references
References 45 publications
10
167
0
Order By: Relevance
“…These characteristics are like those described previously for PHFs and SFs from AD brains 19 . Sarkosyl-insoluble material seeded aggregation of full-length human Tau in cultured cells 20 .…”
Section: Neuropathological Characteristicsmentioning
confidence: 99%
“…These characteristics are like those described previously for PHFs and SFs from AD brains 19 . Sarkosyl-insoluble material seeded aggregation of full-length human Tau in cultured cells 20 .…”
Section: Neuropathological Characteristicsmentioning
confidence: 99%
“…Such leakage may potentially interfere with normal functions of tau, although we have not detected any side effects of that antibody. It was also recently reported that an interaction of a tau antibody with cytosolic Fc receptor, TRIM21, inhibits seeded tau aggregation [65]. This finding suggests that tau antibodies may also have a cytosolic target to facilitate proteosomal clearance of misfolded tau.…”
Section: Toxicity Concernsmentioning
confidence: 82%
“…Finally, the importance of antibody charge for intracellular access has been well studied for potential cancer antibody therapies but not for tau antibodies or similar approaches targeting other amyloids. We have recently shown that antibody charge can robustly affect antibody uptake into neurons [19,64], which may explain why some labs detect tau antibodies inside neurons [2,79,11,12,14,39,40,65], whereas others do not for different antibodies [34,41,43]. This issue has particular importance for clinical trials because the humanized antibodies are likely to have a different charge than the mouse antibodies that they are based on.…”
Section: How Does It Work?mentioning
confidence: 99%
“…Recently, it has been shown that TRIM21 can also inhibit tau seeds, which is the source of pathological tau that exhibits prion-like properties (Iqbal et al, 2015), in a manner similar to neutralizing antibody-bound viruses (McEwan et al, 2017). This suggests that the protection mediated by TRIM21 extends to nonclassical pathogens, such as proteopathic agents.…”
Section: Trim21 Effector Mechanismmentioning
confidence: 99%